Consensus towards partially cooperative strategies in self-regulated evolutionary games on networks - Dario Madeo; Chiara Mocenni (Games, 2021)
Cooperation is widely recognized to be fundamental for the well-balanced development of human societies. Several different approaches have been proposed to explain the emergence of cooperation in populations of individuals playing the Prisoner's Dilemma game, characterized by two concurrent natural mechanisms: the temptation to defect and the fear to be betrayed by others. Few results are available for analyzing situations where only the temptation to defect (Chicken game) or the fear to be betrayed (Stag-Hunt game) is present. In this paper, we analyze the emergence of full and partial cooperation for these classes of games. We find the conditions for which these Nash equilibria are asymptotically stable, and we show that the partial one is also globally stable. Furthermore, in the Chicken and Stag-Hunt games, partial cooperation has been found to be more rewarding than the full one of the Prisoner's Dilemma game. This result highlights the importance of such games for understanding and sustaining different levels of cooperation in social networks.
Keywords: 330; chicken game; complex systems; consensus; cooperation; dynamics on networks; evolutionary games; mixed Nash equilibrium; self-regulation; stable equilibrium; stag-hunt game